2013
DOI: 10.1002/hep.26173
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum polymers impair luminal protein mobility and sensitize to cellular stress in alpha1-antitrypsin deficiency

Abstract: Point mutants of α1-antitrypsin form ordered polymers that are retained as inclusions within the endoplasmic reticulum (ER) of hepatocytes in association with neonatal hepatitis, cirrhosis and hepatocellular carcinoma. These inclusions cause cell damage and predispose to ER stress in the absence of the classical unfolded protein response (UPR). The pathophysiology underlying this ER stress was explored by generating cell models that conditionally express wildtype α1-antitrypsin, two mutants that cause polymer-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
162
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(175 citation statements)
references
References 32 publications
12
162
1
Order By: Relevance
“…Misfolded proteins within the ER lumen usually trigger adaptive measures termed the unfolded protein response (UPR). Indeed, terminally misfolded truncated variants of α 1 -antitrypsin (e.g., α 1 -antitrypsin NullHongKong and Saar) constitutively activate the UPR [32,33]. Surprisingly, the accumulation of Z α 1 -antitrypsin polymers within the ER is not associated with UPR activation in cell lines that recapitulate hepatocyte phenotypes or in transgenic mice, possibly because polymers are structurally ordered (Fig.…”
Section: Intracellular Processing Of α α α α 1 -Antitrypsin Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…Misfolded proteins within the ER lumen usually trigger adaptive measures termed the unfolded protein response (UPR). Indeed, terminally misfolded truncated variants of α 1 -antitrypsin (e.g., α 1 -antitrypsin NullHongKong and Saar) constitutively activate the UPR [32,33]. Surprisingly, the accumulation of Z α 1 -antitrypsin polymers within the ER is not associated with UPR activation in cell lines that recapitulate hepatocyte phenotypes or in transgenic mice, possibly because polymers are structurally ordered (Fig.…”
Section: Intracellular Processing Of α α α α 1 -Antitrypsin Polymersmentioning
confidence: 99%
“…Instead Z α 1 -antitrypsin expression activates NFκB by a calcium-mediated pathway that is independent of the UPR [32][33][34][35]. We have termed this the 'ordered protein response' [35] and others have shown that it results in the release of IL-6 and IL-8 [34].…”
Section: Intracellular Processing Of α α α α 1 -Antitrypsin Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many investigators agree that mutations of the AAT protein can lead to the formation of polymers that are retained within the ER of hepatocytes in ZZ-AATD (3,53), much debate exists regarding the presence of the classical unfolded protein response (UPR), a cellular stress response that leads to attenuation of protein translation and enhancement of ER protein folding in AATD (54,55). Rather, opinion is now moving toward the concept that retention of ordered polymers of AAT within the ER of hepatocytes may predispose cells to ER stress and fully activate the UPR as misfolded protein levels increase (2). Of interest, whereas these findings are well recognized in primary hepatic and various transfected cell line models, the characteristics of ER stress in immune cells from ZZ-AATD patients are less well studied.…”
Section: Discussionmentioning
confidence: 99%
“…AAT deficiency (AATD) is a lethal hereditary disorder characterized by low plasma levels of AAT, with the most common form associated with the Z allele, or homozygous ZZ phenotype (1). Accumulation and disrupted luminal mobility of polymerized aggregates of mutant Z-AAT protein within the endoplasmic reticulum (ER) are implicated in liver cirrhosis and chronic hepatitis (2,3). The most common manifestations of the disease, however, affect the lung, and were initially thought to be due to the loss of the natural antiprotease screen, resulting in early onset emphysema in the ZZ phenotype.…”
mentioning
confidence: 99%